Strategy for Increasing Human Resources Competency in Saving and Loan Cooperatives - Hamid, Abdul (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
The economy controlled by the capitalist system is increasingly peaking, and it still survives to this day, unfortunately there are still very many existing cooperatives that have not been able to progress and develop in accordance with the expectations and goals of the law. This study aims to explain the problems that arise in the development of cooperatives. Then this study discusses things that can improve human resources and promote cooperatives. Qualitative methods with case studies have been used in this study using interviews, observation and analysis of factors that can advance cooperatives in particular in the field of human resources to answer research objectives. Interviews, observations have been carried out in the wrong one sharia cooperative which is the research target. The study that the researchers did was in the form of giving how to increase the competence of human resources in cooperatives. This research finds out how to advance cooperatives through strategies to increase the competence of human resources in cooperatives. In the end, this research provides recommendations on how to advance and develop cooperatives through strategies to increase human resource competence.